Environmental degradation and water quality in urban rivers springs - Machado Garcia, Joice; Mantovani, Paloma; Gomes, Raíssa Caroline; Longo, Regina Marcia; Demamboro, Antonio Carlos; do Carmo Bettine, Sueli (Sociedade & Natureza, 2018)
The quality of a watercourse is directly related to changes in the river basin. The use and occupation of the soil exert a fundamental influence on the surface runoff for these courses, being able to alter its quality and quantity. The district of Barão Geraldo (Campinas/ SP) is part of the Ribeirão das Pedras basin, which is born between Alto Taquaral and Jardim Primavera, and which, after passing through the district headquarters, flows into the left bank of the Anhumas river. This, in turn, ends at the left bank of the Atibaia river, an important river in the state of São Paulo. This work aimed to evaluate the environmental impacts in the springs of the Ribeirão das Pedras basin, in order to verify their quality through the Leopold Matrix and the Water Quality Index (IQA). Through satellite images, topographic charts and field visits, thirteen springs were distributed along the basin, and the IQA was applied to six main springs. The IQA analysis allowed the classification of 5 of the 6 springs as "GOOD", even though they presented irregularities for some parameters. It was verified by the matrix that the most striking parameter in the springs was the non-compliance of the ray of riparian forest, indicating that the measures to be taken preferably at this moment are related to its recovery.